PEMANFAATAN DAUN PEPAYA SEBAGAI PESTISIDA NABATI TERHADAP PENGENDALIAN HAMA BERSAMA IBU-IBU PKK SARIREJO DESA NGELO KECAMATAN CEPU KABUPATEN BLORA - Kunika Ayuana; Dewi Rochmayanti; Sherly Denistawati; Shinta Ayu Zahra Putri; Yeni Sefia Nor Aeni; Bertha Yuvita Anggraeni (LPPM Universitas Almuslim, 2025)
Plant-based pesticides are pesticides derived from plants. Plant-based pesticides are one of the environmentally friendly alternatives to prevent and control pest attacks and plant diseases derived from papaya leaves that contain toxic compounds, namely saponins, alkaloids, carpines, papain, and flavonoids. Community service activities in the form of socialization were held on Wednesday, October 30, 2024 in Ngelo Village, Cepu District, Blora Regency, aiming to provide information and knowledge about the important benefits of using plant-based pesticides. The method of implementing the activities used is using socialization, counseling, and demonstration methods. The results of this activity, as a whole, received a positive response from the PKK women of Ngelo Village. So, it is hoped that through this program, PKK women can understand and apply techniques for making and using plant-based pesticides from papaya leaves. In addition, it can also help reduce environmental pollution, one of which is replacing chemical pesticides with plant-based pesticides.